Varicella Zoster vaccination in hemodialysis patients: The state of the art - Laura Gobbi; Francesca Katiana Martino; Elena Sgrò; Federico Nalesso; Lorenzo A. Calo’ (Human Vaccines & Immunotherapeutics)
Varicella Zoster Virus (VZV) infection is a common childhood exanthematous disease, which in adults and immunocompromised people may result in severe neurologic complications. Up to one-third of infected subjects may have VZV clinical reactivation particularly if immunocompromised. Patients affected by end-stage renal disease on hemodialysis present immunodepression that contributes to their higher incidence of VZV infections and reactivation. While antiviral treatment in these patients shows low efficacy, the prevention of VZV through vaccination avoids the primary infection and the risk of reactivation. Two VZV vaccines are currently available: the live attenuate Zoster Vaccine (LZV) and a Recombinant Zoster Vaccine (RZV), with the latter appearing to provide greater efficacy. Given the higher incidence of VZV infection and reactivation, the lesser response to antivirals and the lower impact of VZ vaccine in hemodialysis patients in terms of side effects, a higher diffusion of VZV vaccination should be promoted by nephrologists in these patients in particular in those with future transplant opportunities.